Political parties in Libya and their impact on the electoral process (1951-2014 AD) - Alham Nouri Al-Sharif (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
This research examines the evolution of political parties in Libya and their impact on the electoral process between 1951 and 2014. The study highlights that the Monarchical era (1951-1969) witnessed a fragile democratic experience characterized by political instability and foreign interference. During this period, parties were often dissolved shortly after formation due to regional fragmentation and low educational levels, leading to their formal prohibition in 1952. In contrast, the military era under Gaddafi (1969-2011) criminalized partisan activity, viewing it as a betrayal of democracy. This forced the political movement to operate from abroad through various organizations such as the National Front for the Salvation of Libya and the Libyan Constitutional Union, which aimed to overthrow the regime. Following the February 17 Revolution, the legal restrictions on political entities were lifted in 2012, resulting in the emergence of numerous parties like the National Forces Alliance and the Justice and Construction Party. The 2012 General National Congress elections utilized a proportional representation system for political lists, where national competence partially overshadowed tribal loyalties. However, the 2014 parliamentary elections shifted back to an individual candidacy system, excluding formal party representation. The study concludes that while post-revolution legislative changes encouraged political pluralism, the deeply rooted tribal structure and the legacy of institutional absence continue to challenge the stabilization of a modern partisan system in Libya.